Myringoplasty for pediatric chronic otitis media: An uncritical closure of a natural middle ear drainage? - Mantsopoulos, Konstantinos; Thimsen, Vivian; Richter, Daniel; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Background: Performing tympanoplasty for tympanic perforations in children and adolescents is often considered to be less successful than in adults. Objectives: The aim of our study was to evaluate the surgical outcome of tympanoplasty type I in patients under 15 years of age with chronic otitis media and to identify potential factors that influence the success rate. Materials und methods: The present study was based on a retrospective analysis of the medical records of all patients under the age of 15 who were treated for chronic otitis media by means of type I tympanoplasty between 2005 and 2020. The minimum follow-up period was 6 months. The data were analyzed with regard to epidemiological parameters, tube-related pathologies in the contralateral ear, the local condition and the extent of the eardrum perforation as well as the extent of the surgical intervention (tympanoplasty type I with or without adenotomy). Results: 83 cases were included in our study. The mean age at the time of the surgery was 8.9 years. The mean follow-up time was 46 months (6–182 months). The anatomical closure rate was 88.0%. Children with “dry” tympanic perforations tended to perform better (p = 0.052). The average improvement in the air bone gap was 2.0 dB. Conclusion: Detailed preoperative counseling about the advantages and disadvantages as well as the expected success rate of an early myringoplasty in this age group is just as important as an individualized approach for a high level of patient satisfaction.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cartilage; Chronic otitis media; Myringoplasty; Tympanic perforation; Tympanoplasty

Risk stratification of thyroid nodules: Assessing the suitability of ChatGPT for text-based analysis - Sievert, Matti; Conrad, Olaf; Müller, Sarina Katrin; Rupp, Robin; Balk, Matthias; Richter, Daniel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (American Journal of Otolaryngology, 2024)
Purpose: Accurate risk stratification of thyroid nodules is essential for optimal patient management. This study aimed to assess the suitability of ChatGPT for risk stratification of thyroid nodules using a text-based evaluation. Methods: A dataset was compiled comprising 50 anonymized clinical reports and associated risk assessments for thyroid nodules. The Chat Generative Pre-trained Transformer (ChatGPT) was used to classify sonographic patterns in accordance with the Thyroid Imaging Reporting and Data System (TI-RADS). The model's performance was assessed using various criteria, including sensitivity, specificity, and accuracy. A comparative analysis was conducted, evaluating the model against investigator-based risk stratification as well as histology. Results: With an overall agreement rate of 42 % in comparison with examiner-based evaluation (TI-RADS 1–5), the results show that ChatGPT has moderate potential for predicting the risk of malignancy in thyroid nodules using text-based reports. The chatbot model achieved a sensitivity of 86.7 %, a specificity of 10.7 %, and an overall accuracy of 68 % when distinguishing between low-risk (TI-RADS 2 and 3) and high-risk (TI-RADS 4 and 5) categories. Interrater reliability was calculated with a Cohen's kappa of 0.686. Conclusion: This study highlights the potential of ChatGPT in assisting clinicians with risk stratification of thyroid nodules. The results suggest that ChatGPT can facilitate personalized treatment decisions, although the agreement rate is still low. Further research and validation studies are necessary to establish the clinical applicability and generalizability of ChatGPT in routine practice. The integration of ChatGPT into clinical workflows has the potential to enhance thyroid nodule risk assessment and improve patient care.
CRIS-Team Scopus Importer:2024-01-19
Keywords: AI; ChatGPT; Risk stratification; Thyroid nodules; Ultrasound

Zufallsbefund Schilddrüsenknoten: Stellenwert der Sonographie und Szintigraphie in der Primärdiagnostik - Richter, Daniel; Beck, Michael; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael; Sievert, Matti (HNO, 2024)
Due to the widespread use of high-resolution sonography, numerous thyroid nodules are diagnosed, often as incidental findings. The challenge lies in evaluating various criteria such as size, shape, and echogenicity to assess the nodules’ malignancy risk. Risk stratification systems have been developed to enable systematic assessment as well as to avoid unnecessary medical interventions and malignant findings being overlooked. This article provides an overview of the current diagnostic standards in primary assessment of thyroid nodules.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Calcitonin; Cytology; Diagnostic imaging; Fine needle aspiration; Thyroid neoplasms